2021
DOI: 10.3390/electronics10232939
|View full text |Cite
|
Sign up to set email alerts
|

FMECA and MFCC-Based Early Wear Detection in Gear Pumps in Cost-Aware Monitoring Systems

Abstract: Gear pump failures in industrial settings are common due to their exposure to uneven high-pressure outputs within short time periods of machine operation and uncertainty. Improving the field and line clam are considered as the solutions for these failures, yet they are quite insufficient for optimal reliability. This research, therefore, suggests a method for early wear detection in gear pumps following an extensive failure modes, effects, and criticality analysis (FMECA) of an AP3.5/100 external gear pump man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Therefore, it is important to determine the problem of motorized spindle failure promptly and select an appropriate maintenance method [31] to reduce the impact of motorized spindle failure on normal production. Figure 10 shows that the signal energy corresponding to the node [3,6] accounts for 84.07%, and the remaining signal energy accounts for less than 10%. It can be observed that the frequency of the original signal is distributed in this node, and the other nodes are the frequency distribution of the noise signal.…”
Section: Vibration Experiments Of Motorized Spindlementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to determine the problem of motorized spindle failure promptly and select an appropriate maintenance method [31] to reduce the impact of motorized spindle failure on normal production. Figure 10 shows that the signal energy corresponding to the node [3,6] accounts for 84.07%, and the remaining signal energy accounts for less than 10%. It can be observed that the frequency of the original signal is distributed in this node, and the other nodes are the frequency distribution of the noise signal.…”
Section: Vibration Experiments Of Motorized Spindlementioning
confidence: 99%
“…Gajanand [2] considered the fuzzy Failure Mode, Effects and Criticality Analysis (FMECA) method to be more suitable for the system criticality problem by comparing traditional and fuzzy FMECA analysis methods. Lee [3] analyzed the fault in a gear pump and explored an intelligent wear detection process based on the Mel-Frequency Cepstrum coefficient. Joanna [4] proposed and discussed a matrix FMEA analysis method and applied it to select hydraulic components.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al [33] established a simulation model of the hydraulic system by using AMESim software and analyzed the failure modes and mechanisms of key components in the system and their failure effects. Lee et al [34] proposed to use FMECA to carry out extensive fault analysis of hydraulic gear pumps and proposed to use MFCC combined with a random forest classifier (RFC) to extract features and identify faults of vibration signals.…”
Section: Fault Analysis Of Hydraulic Pumpmentioning
confidence: 99%
“…In Ref. [25], it is stated that assessing the likelihood of failure, severity level, and detection rate provides a more reliable perspective for prioritizing failure modes as an adjunct to the "classic" addressing the severity of failure modes approach. The methodology proposed in Ref.…”
Section: State Of the Artmentioning
confidence: 99%